Implementation of E-Government to Increase Transparency and Efficiency at the Communication and Information Service (A Case Study in Semarang City) - Tri Widayati, Yohana; Wahyu Binabar, Sattriedi; Widjaja, Stephanus; Saguruk, Thepanus (Computing and Information System Journal, 2025)
The advancement of information technology has encouraged local governments to adopt e-Government systems to improve the quality of public services. This study aims to analyze the implementation of e-Government at the Department of Communication and Informatics (Diskominfo) of Semarang City through the Sapa Mbak Ita application as a public complaint platform. The research was conducted using observation, interviews with the Head of the Department, literature review, and a system development approach based on the waterfall model. The results show that the citizens of Semarang actively use various digital complaint channels, with the highest number of reports submitted via WhatsApp and the Sapa Mbak Ita mobile application. Out of 6,129 reports received in 2023, the majority were followed up. However, several issues were identified, including delayed complaint resolution and user concerns regarding ease of use and the security of personal data. This study concludes that Sapa Mbak Ita has contributed positively to enhancing public service transparency, although improvements are still needed in terms of efficiency and user data protection.